2017
DOI: 10.2337/db16-1225
|View full text |Cite
|
Sign up to set email alerts
|

Fat-Specific Sirt6 Ablation Sensitizes Mice to High-Fat Diet–Induced Obesity and Insulin Resistance by Inhibiting Lipolysis

Abstract: Sirt6 is an NAD-dependent deacetylase that is involved in the control of energy metabolism. However, the tissue-specific function of Sirt6 in the adipose tissue remains unknown. In this study, we showed that fat-specific Sirt6 knockout (FKO) sensitized mice to high-fat diet-induced obesity, which was attributed to adipocyte hypertrophy rather than adipocyte hyperplasia. The adipocyte hypertrophy in FKO mice likely resulted from compromised lipolytic activity as an outcome of decreased expression of adipose tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
98
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 43 publications
8
98
1
Order By: Relevance
“…Sirt6 deficiency results in mice metabolic defects, and Sirt6 transgenic mice accumulate less fat, cholesterol, and triglycerides after HFD treatment . A previous study has demonstrated that Sirt6 expression is reduced in obese patients, and fat‐specific Sirt6 deficiency increased inflammation and insulin resistance in HFD‐treated mice . In this study, we demonstrated that USP10 interacts with Sirt6 and inhibits its ubiquitination and degradation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Sirt6 deficiency results in mice metabolic defects, and Sirt6 transgenic mice accumulate less fat, cholesterol, and triglycerides after HFD treatment . A previous study has demonstrated that Sirt6 expression is reduced in obese patients, and fat‐specific Sirt6 deficiency increased inflammation and insulin resistance in HFD‐treated mice . In this study, we demonstrated that USP10 interacts with Sirt6 and inhibits its ubiquitination and degradation.…”
Section: Discussionsupporting
confidence: 56%
“…(29) A previous study has demonstrated that Sirt6 expression is reduced in obese patients, and fat-specific Sirt6 deficiency increased inflammation and insulin resistance in HFD-treated mice. (30,31) In this study, we demonstrated that USP10 interacts with Sirt6 and inhibits its ubiquitination and degradation. Then, we established Sirt6-KO, Sirt6-TG, USP10-TG/Sirt6-KO, and USP10-KO/Sirt6-TG mice and performed HFD treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, insulin resistance in skeletal muscle plays a vital role in the onset of diabetes [Ferrannini et al, 1985]. Numerous studies including clinical researches and animal experiments illustrated that adipocyte hypertrophy rather than its hyperplasia led to insulin resistance [Kuang et al, 2017]. As for adipose tissue, it plays an important role not only in glucose metabolism but also in endocrine.…”
Section: Discussionmentioning
confidence: 99%
“…As an endocrine organ, adipose tissue can secrete a type of cytokines related to inflammatory response, insulin resistance and cardiovascular diseases, such as leptin, adiponectin, resistin, TNFa, and visfatin [Antuna-Puente et al, 2008]. Numerous studies including clinical researches and animal experiments illustrated that adipocyte hypertrophy rather than its hyperplasia led to insulin resistance [Kuang et al, 2017]. In our study, with StAR overexpression, the surface area of adipocytes and intramuscular lipid accumulation were remarkably decreased, as well as the enhanced blood glucose and insulin levels by HFD were significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Sirt6 controls metabolic homeostasis and is regulated by nutrient availability (26,27). To investigate whether Sirt6 plays a role in ketogenesis, we measured the hepatic Sirt6 expression in mouse models of ketogenesis.…”
Section: Sirt6 Is Regulated By Ketogenesismentioning
confidence: 99%